Viscosity Behavior of Solutions of Some Potassium Salts in Dimethyl Sulphoxide –Water mixture - Ahlam M. Farhan; Sahar S. Hassan; Souad A. Mousa (مجلة بغداد للعلوم, 2010)
The present work includes a study of viscosity of solutions containing Potassium Chloride and Potassium Bromide in Dimethyl Sulphoxide and water as solvent (containing 60% w/w DMSO).